MAKING CORN FLOURING MACHINE WITH ANTHROPOMETRY APPROACH - Subchan Asy'ari; Abdul Wahid (Universitas Darussalam Gontor, 2019)
The process of sifting corn flour in the home of the gerit rice industry in Pasuruan Regency was carried out manually and the equipment used was not ergonomic. workers also have to reach the sifted cornmeal at different places. The purpose of this study was carried out with the aim to produce an ergonomic corn flour sieving tool to facilitate workers in the process of corn flour sifting in micro rice business in all regions of Pasuruan Regency and reduce excessive fatigue.This research was conducted to obtain the target specifications for the design of corn flour sieving aids for the manufacture of rice grind in the Pasuruan Regency area in accordance with the Anthropometric approach and the physical form of the worker. Anthropometric data collection was carried out randomly and 30 sample / person data were taken from all the gerit rice home industries in Pasuruan Regency. From the results of data processing to determine the dimensions / size of the grilled rice flour sieve worker is the height of the standing leg position is P95 = 92.2, and the forearm reach is P95 = 75.2.With the presence of an ergonomic corn flour sieving machine, workers can more easily carry out the process of sifting corn flour compared to using a manual corn flour sieving tool. By using an ergonomic cornmeal sieving machine, workers do not move much just by inserting raw materials into the sieving machine and waiting for the sifting process to finish, this can reduce the workload and fatigue of workers. Keywords: Corn Flour Sieving Machine, Ergonomic, Anthropometry.